2019
DOI: 10.1111/os.12467
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Pedicle Cement Augmentation with Proximal Screw Toggle and Loosening

Abstract: Background Cement augmentation is a technique used to increase the stability and purchase of pedicle screws in poor quality bone. Various methods can be applied for cement delivery, such as cement injection before screw placement and the use of fenestrated screws. However, potential problems can arise with the use of cement augmentation. Case Presentation A 66‐year‐old man with a lower trunk deformity, severe kyphosis, and sagittal imbalance following fusion (L2‐5), with minimal comorbidities, was referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…[ 19 ] The use of cement-augmented pedicle screws is easy and feasible, although biomechanical failure can occur if an inadequate amount of bone cement is used or cemented screws are misplaced. [ 24 ] In a series of studies, loosening rate was significantly lower in cement-augmented pedicle screws (4.3%) than noncemented screws (62.8%). [ 25 ] There have been recent reports on the clinical efficacy of cement augmentation using fenestrated screws.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] The use of cement-augmented pedicle screws is easy and feasible, although biomechanical failure can occur if an inadequate amount of bone cement is used or cemented screws are misplaced. [ 24 ] In a series of studies, loosening rate was significantly lower in cement-augmented pedicle screws (4.3%) than noncemented screws (62.8%). [ 25 ] There have been recent reports on the clinical efficacy of cement augmentation using fenestrated screws.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are made using a cadaver. As such, the clear outcomes clarifying the issues of osseointegration and bone remodeling are not applicable due to the use of cadaveric bones that lack any healing potential [77].…”
Section: Discussionmentioning
confidence: 99%
“…In the PMMA technique, the pivot point of the screw is shifted ventrally into the vertebral body [ 17 ]. The limited stability of the augmented screws detected in the fatigue test and the biomechanical changes explain the proximal loosening observed after PMMA augmentation [ 18 ]. The results showed that PMMA augmentation did not completely solve the problem of pedicle screw instability development, since a significant number of proximal loosening cases became apparent.…”
Section: Discussionmentioning
confidence: 99%